Upaya Meningkatkan Hasil Belajar IPA Siswa Kelas V SD Negeri Dawuan Tengah 1 Melalui Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) pada Pokok Bahasan Ekosistem - Febi Tresna Wahyuni (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This study aims to explore the implementation of Lesson Study with the Realistic Mathematics This Classroom Action Research (CAR) focuses on enhancing Science learning outcomes among fifth-grade students at SD Negeri Dawuan Tengah 1, particularly in the topic of Ecosystem. The study employs the Teams Games Tournament (TGT) teaching method across multiple cycles. Pre-cycle assessment revealed low achievement rates, prompting a shift from conventional teaching methods to TGT. Results indicate a significant improvement in student performance over successive cycles, with 80% meeting the Minimum Mastery Criteria (KKM) by the second cycle. Analysis suggests that TGT fosters a more engaging and participatory learning environment, addressing student disinterest and fear towards Science. The findings underscore the importance of innovative teaching approaches in enhancing student learning outcomes, with implications for curriculum design and pedagogical practices.